2021
DOI: 10.1177/00368504211016214
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric assessment of the mesorectal fat in Chinese Han population: A clinical MRI study

Abstract: The study aimed to analyze morphometric assessment of the mesorectal fat thickness and its correlation with body mass index in Chinese Han population. The anterior, posterior, right lateral, and left lateral mesorectal fat thickness were measured using MRI T2-weighted images. The mean distance from the rectal wall to the mesorectal fascia were 3.8, 8.4, 11.3, and 11.7 mm in anterior, posterior, right lateral, and left lateral portion, respectively. The mesorectal area, rectal area, mesorectal fat thickness are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
1
2
1
Order By: Relevance
“…It was reported that viscerally obese patients with rectal cancer were more likely to be male [ 37 ], which was consistent with our results. Two other studies measured PFA using pelvic CT/MR images and found that PFA positively correlated with BMI [ 23 , 40 ], which was consistent with our results. Both BMI and VAT were prognostic factors for OS and DFS in CRC patients [ 17 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It was reported that viscerally obese patients with rectal cancer were more likely to be male [ 37 ], which was consistent with our results. Two other studies measured PFA using pelvic CT/MR images and found that PFA positively correlated with BMI [ 23 , 40 ], which was consistent with our results. Both BMI and VAT were prognostic factors for OS and DFS in CRC patients [ 17 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 92%
“…PFA, as the closest part of the VAT surrounding the rectum, was speculated to play an active role in the carcinogenesis and progression of rectal cancer. Tripathi et al reported that the mean PFA in a Chinese Han population, measured using pelvic MR images, was 24:0 ± 6:9 cm [23], which was higher than the mean PFA (20:4 ± 6:9 cm 2 ) in our study. This may have been caused by the difference in the series of MR images selected for measurement; they selected T2weighted images, and we selected the fat series images.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…One possible reason may be that EMD is limited by the tumor’s location (high or low rectal cancer), actually by the mesorectum thickness. A clinical MRI study of 183 Chinese reported that the mean mesorectum thickness was found to be <12 mm, suggesting that the existing EMD-based T3 substage including 15 mm may not suitable for Chinese population because of relatively thin mesorectum thickness ( 26 ). In this study, 55.6% (160/288) of T3a/b tumors were located at the lower rectum, while only 46.2% (122/264) of T3c/d tumors were located at the lower rectum.…”
Section: Discussionmentioning
confidence: 99%